Genomic Assessment of Enterobacter mori AYS9: A Potential Plant Growth-Promoting Drought-Resistant Rhizobacteria - Ayomide Emmanuel Fadiji; Ayansina Segun Ayangbenro; Olubukola Oluranti Babalola (Spanish Journal of Soil Science)
Drought stress poses a serious danger to agricultural production. Recent studies have revealed that most of the chemical methods used in the mitigation of its effects on plant production pose a serious threat to humans and the environment. Therefore, the demand for ecologically friendly solutions to ensure the security of the world’s food supply has increased as a result. Plant growth-promoting rhizobacteria (PGPR) treatment may be advantageous in this situation. Enterobacter mori is a promising rhizobacteria in this regard. However, information on the genome analysis of E. mori linked to the rhizosphere soil of the sorghum plant has not been extensively studied. In this study, we present a genomic lens into functional attributes of E. mori AYS9 isolated from sorghum plants, as well as assess its drought tolerance and plant growth-promoting potentials. Our results showed the drought tolerance and plant growth-promoting potentials of the AYS9. Whole genome sequencing (WGS) results revealed that the genome yielded 4,852,175 bp sequence reads, an average read length of 151 bp, 1,845,357 bp genome size, 67 tRNAs, 3 rRNAs, and a G + C content of 55.5%. The functional genes identified in the genome were linked to processes including phosphate solubilization, iron transport, hormone regulation, nitrogen fixation, and resistance to oxidative and osmotic stress. Also, secondary metabolites supporting bacterial biocontrol properties against phytopathogens, and abiotic stress such as aerobactin-type non-ribosomal peptide siderophore, Stewartan-type ladderane, and Colicin type NRPS were discovered in the AYS9 genome. Our findings however establish that the intricate metabolic pathways mediated by the projected new genes in the bacterial genome may offer a genetic foundation for future understanding of rhizosphere biology and the diverse roles that these genes play in plant development and health.